Teaching model development to enhance the creativity for college students in China - Huang, Jieqi; Chookhampang, Chowwalit; Chano, Jiraporn (Frontiers in Education, 2025)
Creativity, a core competency for self-awareness and problem-solving, remains underdeveloped among Chinese college students, primarily due to insufficient emphasis on innovation cultivation in education. The main purposes of this research are to develop, implement a teaching model based on the cognitive approach to enhance the creativity for college students. The model was designed utilizing 4 main components of “Problem-Ideation-Prototype-Testing” (PIPT) and implemented with 60 freshmen at Guangzhou Panyu Polytechnic, China. The samples were drawn from a cluster sample and formed a quasi-experimental design. Students were divided into an experimental group and a control group for independent samples t-tests and paired samples t-tests. The data was analyzed using questionnaires, creativity assessments, and t-tests. The results revealed that the PIPT model with 6 main components:principles, objectives, syntax, social systems, reactions, and support systems, achieved a teaching evaluation score of 4.61, was at the highest level of applicability. Independent and paired t-tests demonstrated the model's superiority over traditional methods in enhancing creativity (p < 0.05), affirming its efficacy in achieving educational goals and fostering student creativity.